Implementation of cleaner production in the refined sugar industry to reduce landfilling in waste management at sugar industry in Cilegon - Prio Utomo; Fatah Sulaiman; Juwarin Pancawati (OPSI, 2026)
Sugar Industry in this study  is a company located in Cilegon City, Banten Province, operating in the refined sugar industry. The objective of this study is threefold: first, to identify the flow of materials, products, and non-products in the refined sugar production process; second, to identify potential cleaner production alternatives applicable to the industry; and third, to determine the priority scale of cleaner production opportunities in the refined sugar industry. The research methods employed encompass a comprehensive array of approaches, including a thorough literature review, observational studies, environmental assessments, and comparative analyses. According to the findings of the research study, the total amount of waste generated in 2023 was 19,025.36 tons. Of this, 5,575.52 tons (29.3%) were landfilled, and 13,449.84 tons (70.7%) were reused by other industries. In 2024, the total waste generated was 16,579.35 tons, of which 16,568.44 tons were utilized by other industries as alternative fuel or alternative raw materials, and a mere 10.91 tons were sent to landfill. According to the 2024 data, a mere 0.07% of the total waste was landfilled, while a staggering 99.7% was reused by other companies. The implementation of cleaner production and zero-landfill principles has the potential to repurpose the waste generated.